The Development of De Djawatan Local Potential-Based E-Module for Science Learning to Improve Science Process Skills of Junior High School Students - Dian Fajar Nuryah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2022)
Science process skills are the ability to study natural phenomena in certain ways to acquire knowledges and develop it in the future. Students who have science process skills will be able to solve problems, form concepts, and be able to develop creativity. Based on the previous studies, science process skills in science learning are still low. One of the factors that cause the low science process skills is the lack of teaching materials that facilitate the development of students' science process skills. One of the factors that cause students' science process skills to be low is the lack of teaching materials that facilitate the development of students' science process skills. This study aims to develop an De Djawatan's local potential-based e-module that is valid, practical, and effective to improve students' science process skills. This research was conducted according to the stages in the ADDIE model, namely analyze, design, develop, implement, and evaluate. The results of the study show that the local potential-based e-modules are included in the following criteria: (1) valid with a value of 85%; (2) very practical with a value of 89.2%; and (3) effective with moderate improvement category. Students showed a positive response with a percentage of 86%.